A Study to Evaluate the Relationship of Estimated Fetal Weight and Actual Fetal Birth Weight Using Ultrasound: Estimated Fetal Weight and Actual Fetal Birth Weight Using Ultrasound - Khalid, Pakeeza; John, Akash; Ali, Abid; Khalid, Sundas (Pakistan Journal of Health Sciences, 2022)
Estimated fetus weight is an essential measurement used to predict the fetal health during pregnancy as it has a close correlation with fetal mortality, Low fetal weight can lead to IUGR and high fetal weight can lead to fetal and maternal complications. Objective: To assess the changes among Estimated fetus weight and Actual fetus weight after birth. Methods: This cross-sectional study was conducted in the obstetric and gynecological sector of tertiary care setup in Gujrat, Pakistan. The data was collected for the duration of 4 months from December 2021 to March 2022. Data was collected using a convenient sampling technique. A sample size of 169 patients was calculated using the mean from previous related published studies. A Toshiba ultrasound machine was used with a 3.5 MHz convex probe was used. Data analysis was done by SPSS version 20. Consent was taken from all the participating pregnant females. Results: In this study result mean of estimated fetal weight (g) in the 3rd trimester was 2690.72 ± 463.97g the average of actual weight (g) gained after delivery was 2701.04 ± 483.24g. The paired t-test shows no significant change in estimated fetus weight on ultrasound and actual fetus weight after birth. Conclusion: This study determined that estimated fetal weight can be measured using an advanced ultrasound machine which can be cost-effective. This study also concluded that the difference among estimated fetus weight and actual fetus weight after birth is not statistically significant.